CONTROL OF ERINNYIS IT (L) (Lep: Sphingidae) YUCCA CUTWORM Worm Manihot esculenta (Crantz) WITH Baculovirus erinnyis NGV. - ARIAS-V., BERNARDO (Revista Colombiana de Entomología, 1987)
The cassava hornworm Erinnyis ello can cause yield reduction up to 64% depending upon plant age, number of attacks, and agroecological conditions. The virus Baculovirus erinnyis is one of 30 natural enemies reported for cassava hornworm. B. erinnyis constitutes a potential control agent since it can reduce pest populations below the economic threshold. Experiments were conducted at CIAT to determine the effect of B. erinnyis when used fresh, refrigerated for 4 years, and stored in powder form for 2 years at room temperature. The virus was applied in the field on experimental plots and under laboratory conditions on cassava leaves at 30.0, 6.0, and 0.269/o concentrations. Isolation, purification, and storage methods were studied to facilitate the virus practical use by farmers. Results show that B. erinnyis can be obtained from infected larvae by easy methods and can be applied by conventional methods to obtain significant control at 72 and 161 hours after application.